Role of Sulphur nutrition in oilseed crop production - A review (Journal of Oilseed Brassica, 2026)
Sulphur is an essential nutrient for the production of oilseeds. It is the 13th most abundant element in the earth’s crust with an average concentration of 0.06 percent. It is necessary for the synthesis of proteins, oils, and vitamins. Agricultural soils have a low concentration of inorganic sulfur compared to the organic form. A sulfur deficiency also leads to a 40 percent reduction in the quality and quantity of rapeseed or oilseeds. Sulfur deficiency is becoming very common in many states of India. In previous years, various studies on sulfur have been carried out, viz. factors that affect the availability of Sulphur to plants, its function in the plant, the response of Sulphur in various crops, etc. The objective of this review is to provide an update on recent discoveries related to these topics, which may contribute to a better understanding of S fertilization and the role of S in oilseeds.